Morbidities and Outcome of a Neonatal Intensive Care in Western Nepal - Adhikari, Sudhir; Rao, Kalipatanam Seshagiri; B.K., Ganesh; Bahadur, Namraj (Journal of Nepal Health Research Council, 2017)
Background: Neonatal mortality rate of developing countries is declining over decades. In the recent years increasing number of preterm and high risk neonates have facilities for tertiary care treatment. The aim of the study was to assess the morbidities and outcome of neonatal intensive care admissions. Methods: It was a retrospective observational study carried out in neonatal intensive care unit of the Manipal Teaching Hospital, Pokhara, Nepal from January 2014 to December 2015. Neonatal details including place of delivery, birth weight, gestation, diagnosis at admission, hospital course and final outcome were recorded in predesigned proforma. Risk of mortality was calculated using odds ratio and 95% confidence interval. Results: There were total 1708 admission during study period and inborn as well as out born neonates were equally admitted. Neonatal hyperbilirubinemia (37.1%), neonatal sepsis 532 (31.2%), prematurity, 314 (18.4%) perinatal asphyxia 112 (6.6%), meconium aspiration syndrome 79 (4.6%) and intrauterine growth restriction 49 (2.8%) were main indications for hospitalization. A total of 1410 (82.6%) the patients were discharged after treatment, 167 (9.7) left against medical advice, 115 (6.7%) died in hospital and 16 (1%) cases were referred. Preterm neonates had twice the risk of mortality than term neonates (OR =2.1664). Birth weight < 2500 grams had three times more risk of neonatal mortality than normal birth weight (OR =3.0783). Conclusions: Neonatal hyperbilirubinemia, prematurity and neonatal sepsis were common morbidities inneonatal intensive care unit.